Juridical Review of Law No. 21 of 2007 Concerning Trafficking in Persons in a Transnational Sphere - Sugiawan, Fricila Anggitha; Arrasyid, Muhhammad Restu (CV. Rayyan Dwi Bharata, 2023)
Trafficking in persons is a serious human rights violation and damages the lives of millions of people around the world. Trafficking in persons is also an organized and systematic crime, in which the people involved have personal or group interests to gain profit. Trafficking victims may be kidnapped, or they may be coerced or tricked into promises of better jobs, education, or other opportunities. Once trapped in human trafficking networks, victims can be used as sex slaves, housework, the sex industry, or even organ harvesting. This research method uses a juridical-normative approach which is focused on examining the applications, principles or norms in applicable law. Data is obtained from the collection of laws, books, articles, journals that are related to the problem under study. The results obtained show that trafficking in persons occurs in every country, the regulations for this matter are Law no. 21 of 2007 in Indonesia can be said to be lacking. Public awareness is also needed in overcoming this.